2018
DOI: 10.1038/s41598-017-18790-0
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic in vivo evaluation of the time-dependent inflammatory response to steel and Teflon insulin infusion catheters

Abstract: Continuous subcutaneous insulin infusion (CSII) catheters are considered the weak link of insulin pump therapy. Wear-time considerably varies between patients and the choice of catheter material is based on personal preferences rather than scientific facts. Therefore, we systematically assessed and quantified the inflammatory tissue response to steel versus Teflon CSII catheters over a maximum wear-time of 7 days in swine. Tissue surrounding catheters was analysed using histopathology and quantitative real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…[3,31] Herein, we implanted sterilized NO-releasing and control Pebax 7233 tubes (2 cm length under the skin, ~30° insertion angle) into subcutaneous tissue of the sheep and used these tubes as cannula to deliver insulin. Like many other projects on diabetes management technologies, [12, 31ab] this work employed healthy rather than diabetic animals as the first step because diabetic animals are difficult to handle and also much more expensive to use as test animals. However, the anti-inflammatory property of NO in type 1 diabetic animals has been confirmed very recently by the Schoenfisch group, [31c] suggesting that benefits originating from suppressed inflammation may not be limited to only non-diabetic animals.…”
Section: Resultsmentioning
confidence: 99%
“…[3,31] Herein, we implanted sterilized NO-releasing and control Pebax 7233 tubes (2 cm length under the skin, ~30° insertion angle) into subcutaneous tissue of the sheep and used these tubes as cannula to deliver insulin. Like many other projects on diabetes management technologies, [12, 31ab] this work employed healthy rather than diabetic animals as the first step because diabetic animals are difficult to handle and also much more expensive to use as test animals. However, the anti-inflammatory property of NO in type 1 diabetic animals has been confirmed very recently by the Schoenfisch group, [31c] suggesting that benefits originating from suppressed inflammation may not be limited to only non-diabetic animals.…”
Section: Resultsmentioning
confidence: 99%
“…Although several factors might induce inflammation at the infusion site, the specific mechanisms underlying CSII device failure have yet to be determined. Various hypotheses have been generated including mechanical barriers to insulin flow and direct toxicity from the infusion device's composition 12,15,16,28 . However, this study focused on the root causes of the inflammatory response, specifically the phenolic compound used in insulin formulations, as well as the specific cell types responsible for the inflammation induced by these insulin phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Hauzenberger et al reported that inflammation might function as a mechanical barrier to insulin flow in a swine model 12 . In addition, Teflon versus steel catheter materials were compared in order to determine the specific effects of material‐induced inflammation at CSII sites, but no significant differences were observed 13‐16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we combined micro-CT imaging, histopathology and insulin tubing pressure analysis to investigate the progression of the inflammatory tissue response to straight and angled CSII catheters over time in a non-diabetic swine model. This animal model has been successfully used in prior studies by our group and collaborators,12 13 and has been shown to be the most adequate for human skin and adipose tissue wound healing 14. We hypothesized that the change in thickness of the layer of acute and chronic inflammatory tissue surrounding the cannula of a CSII catheter has a direct effect on insulin spread (bolus volume and surface area) and tubing pressure.…”
Section: Introductionmentioning
confidence: 99%